A new efficient checkpointing algorithm for distributed mobile computing - Mansouri, Houssem; Badache, Nadjib; Aliouat, Makhlouf; Pathan, Al-Sakib Khan (Romanian Society of Control Engineering and Technical Informatics, 2015)
Mobile networks have been quickly adopted by many companies and individuals. However, multiple factors such as mobility and limited resources often constrain availability and thus cause instability of the wireless environment. Such instability poses serious challenge for fault tolerant distributed mobile applications. Therefore, the classical checkpointing techniques, which make the applications more failure-resistant, are not always compatible with the mobile context. In fact, it is necessary now to think about other techniques or at least adapt those to devise effective and well suited techniques for the mobile environment. Considering this issue, the contribution in this paper is a proposal of a new checkpointing algorithm suitable for mobile computing systems. This algorithm is characterized by its efficiency and optimization in terms of incurred time-space overhead during checkpointing process and normal application running period.